Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.dcn.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Social network size relates to developmental neural sensitivity to biological motion

Abstract: The ability to perceive others' actions and goals from human motion (i.e., biological motion perception) is a critical component of social perception and may be linked to the development of real-world social relationships. Adult research demonstrates two key nodes of the brain's biological motion perception system-amygdala and posterior superior temporal sulcus (pSTS)-are linked to variability in social network properties. The relation between social perception and social network properties, however, has not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…More importantly, this study, for the first time, confirmed the positive correlation between interactive BM perception and social competence, especially in older children aged 5–6 years. Although previous studies have found that children's monadic BM processing was related to their social cognitive abilities (He et al, 2018; Rice et al, ) and social competence (Endedijk et al, ; Kirby et al, ; Krogh‐Jespersen et al, ), the current results highlight the potential relation of social interaction perception on children's social development. The finding is consistent with a previous study in which the understanding of interactive actions positively predicted empathizing ability in school‐aged children (Ghanouni et al, ).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…More importantly, this study, for the first time, confirmed the positive correlation between interactive BM perception and social competence, especially in older children aged 5–6 years. Although previous studies have found that children's monadic BM processing was related to their social cognitive abilities (He et al, 2018; Rice et al, ) and social competence (Endedijk et al, ; Kirby et al, ; Krogh‐Jespersen et al, ), the current results highlight the potential relation of social interaction perception on children's social development. The finding is consistent with a previous study in which the understanding of interactive actions positively predicted empathizing ability in school‐aged children (Ghanouni et al, ).…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have demonstrated that intention inference (e.g., theory of mind, emotion understanding), which rapidly develops during preschool stage, has immense value for young children's effective social adaptation (Denham et al, ; Devine, White, Ensor, & Hughes, ; Peterson & Siegal, ; Slaughter, Dennis, & Pritchard, ). Relevant developmental research focused on action perception involved in monadic PLD BM or real‐world contexts has found that better perception of human BM predicts higher social cognitive ability (e.g., theory of mind; Burnside, Wright, & Poulin‐Dubois, ; He et al, ; Rice, Anderson, Velnoskey, Thompson, & Redcay, ) and superior social competence (e.g., larger social network, better peer cooperation; Endedijk, Meyer, Bekkering, Cillessen, & Hunnius, ; Kirby, Moraczewski, Warnell, Velnoskey, & Redcay, ; Krogh‐Jespersen, Liberman, & Woodward, ). However, despite the ability to perceive the actions of others, precisely interpreting underlying shared intentions and interpersonal relationships in peer interactions may be more important if a child wants to have effective social interactions and to be well accepted.…”
Section: Introductionmentioning
confidence: 99%
“…The pSTS, on the other hand, has traditionally been associated with the visual perception of biological motion (66)(67)(68)(69) and social interactions (70)(71)(72) , and is considered part of a third visual pathway that is specialized for social information (73).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, the individual at the center of a network must have a strong ability to identify obscure social signals in order to play a complex social role (Dziura and Thompson, 2014). Accordingly, Kirby et al (2018) investigated neural sensitivity to biological motion related to social network properties in middle childhood. Consistent with the study by Dziura, the children's social network size (the number of people the child regularly sees or talks to), diversity (the number of social roles the child plays) and embeddedness (the number of social domains in which the child is active) predicted activation in the pSTS, which significantly correlated with the neural sensitivity to biological motion when the children viewed biological motion.…”
Section: The Mirror Neuron Systemmentioning
confidence: 99%
“…For example, social network analysis provides a deeper understanding of social complexity by directly measuring the number or types of social relationships. Overwhelming evidence indicates that the complexity of the social network structure is positively correlated with social skills, such as sociability, mentalizing or encoding biological motion (Wey et al, 2008;Kirby et al, 2018;Gentina et al, 2020). Based on a complete map of the asocial network of interaction units, the social network can also describe the source and amount of social influence (e.g., social support, conformity, imitation and compliance) perceived by individuals (Blumen and Verghese, 2018;Bang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%